Profile analysis of patients with dizziness in a tertiary hospital in Rio Grande do Norte (Research, Society and Development, 2020)
Objective: to provide a profile of patient with dizziness complaint in a terciary hospital in Rio Grande do Norte (RN). Methods: 444 medical records were analyzed in a retrospective analytical study, within a quantitative approach, divided into four groups: sex and age (1), characteristics of dizziness (2), comorbidities and risk factors (3) and findings in the physical examination (4). We assign p